Holocene prehistory in the Télidjène Basin, Eastern Algeria : Capsian occupations at Kef Zoura D and Aïn Misteheyia - Lubell, David (Archaeopress, 2016)
Kef Zoura D and Aïn Misteheyia are stratified Capsian escargotières (one openair, the other a rockshelter) in the Télidjène Basin, Eastern Algeria. They were excavated in the 1970s but have remained incompletely published. The sites are the only modern excavations of a Capsien Typique/Capsien Supérieur sequence, demonstrating that this is indeed a chronological progression related to the 8200 cal BP climate event. The technological (introduction of pressure flaking), palaeoeconomic and palaeoecological changes related to this event are examined in these contributions.